Zooming in on the circumgalactic medium with GIBLE: tracing the origin and evolution of cold clouds - Ramesh, Rahul; Nelson, Dylan; Fielding, Drummond; Brüggen, Marcus (Astronomy and astrophysics, 2025)
We used the GIBLE suite of cosmological zoom-in simulations of Milky Way-like galaxies with additional super-Lagrangian refinement in the circumgalactic medium (CGM) to quantify the origin and evolution of CGM cold gas clouds. The origin of z = 0 clouds can be traced back to recent (≲2 Gyr) outflows from the central galaxy (∼45%), condensation out of the hot phase of the CGM in the same time frame (∼45%), and to a lesser degree to satellite galaxies (≲5%). We find that in situ condensation results from rapid cooling around local overdensities primarily seeded by the dissolution of the previous generation of clouds into the hot halo. About ≲10% of the cloud population is long-lived, with their progenitors having already assembled ∼2 Gyr ago. Collective cloud-cloud dynamics are crucial to their evolution, with coalescence and fragmentation events occurring frequently (≳20 Gyr−1). These interactions are modulated by non-vanishing pressure imbalances between clouds and their interface layers. The gas content of clouds is in a constant state of flux, with clouds and their surroundings exchanging mass at a rate of ≳103 M⊙ Myr−1, depending on cloud relative velocity and interface vorticity. Furthermore, we find that a net magnetic tension force acting against the density gradient is capable of inhibiting cloud-background mixing. Our results show that capturing the distinct origins of cool CGM clouds, together with their physical evolution, requires high-resolution cosmological galaxy formation simulations with both stellar and supermassive black hole feedback-driven outflows.